Odpowiedzi

2010-01-26T19:32:29+01:00
A) abc-(abc-(-xyz-(xyz-abc)))= abc-(abc-(-xyz-xyz+abc))= abc-(abc+xyz+xyz-abc)= abc-abc-xyz-xyz+abc= -2xyz+abc

b) s*st-(st*st-(s*st-(st*st-s*st)))= s*st-(st*st-(s*st-st*st+s*st))= s*st-(st*st-s*st+st*st-s*st)= s*st-st*st+s*st-st*st+s*st= 3s*st-2st*st

c)x*x yz-(xy*xy z -(xyz*xyz-(x*x yz- xy*xyz)))= x*x yz-(xy*xy z -(xyz*xyz-x*xyz+xy*xyz))= x*x yz-(xy*xy z -xyz*xyz+x*xyz-xy*xyz)= x*x yz-xy*xy z+xyz*xyz-x*xyz+xy*xyz= xyz*xyz
  • Użytkownik Zadane
2010-01-26T22:24:01+01:00
A) abc-(abc-(-xyz-(xyz-abc)))= abc-(abc-(-xyz-xyz+abc))= abc-(abc+xyz+xyz-abc)= abc-abc-xyz-xyz+abc= -2xyz+abc

b) s*st-(st*st-(s*st-(st*st-s*st)))= s*st-(st*st-(s*st-st*st+s*st))= s*st-(st*st-s*st+st*st-s*st)= s*st-st*st+s*st-st*st+s*st= 3s*st-2st*st

c)x*x yz-(xy*xy z -(xyz*xyz-(x*x yz- xy*xyz)))= x*x yz-(xy*xy z -(xyz*xyz-x*xyz+xy*xyz))= x*x yz-(xy*xy z -xyz*xyz+x*xyz-xy*xyz)= x*x yz-xy*xy z+xyz*xyz-x*xyz+xy*xyz= xyz*xyz